Pengaruh Tingkat Pengangguran Dan Tingkat Upah Minimum Provinsi Terhadap Tingkat Kemiskinan Di Provinsi Riau - Vinny Alvionita Riva; Hainim Kadir; Deny Setiawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Poverty is a complex and complicated issues that require analysis in order to obtain a solution to overcome poverty or at least reduce poverty. This study aimed to examine the effect of the unemployment rate and the level of the minimum wage on poverty levels in Riau province. This research uses secondary data. Analysis of the data in this study using a multiple linear regression method. Hypothesis testing using partial test (t test), simultaneous (F test), Test Correlation Coefficient (R) and test the coefficient of determination (R2). The data used in this study are data on the number of poor people, the number of unemployed and the level of the minimum wage in the province of Riau Province in 2002-2011. The results of the testing that has been done, the entire regression test showed that all independent variables have a significant effect on the dependent variable. Individual regression test showed that the number of open unemployment has no significant effect on the number of poor people in Riau province, but the provincial minimum wage have a significant effect on the number of poor people of Riau Province. The magnitude of the effect caused by the two independent variables together on the dependent variable of 92.1%, while the remaining 8.8% is influenced by other variables not examined in this study.Keywords: Poverty, Unemployment, Province Minimum Wage.